Romantic Love and Family Organization - Victor de Munck; Andre Korotayev; Jennifer McGreevey (Evolutionary Psychology)
We propose that romantic love is a biosocial phenomenon that may well be a universal and that its cultural aspects are a product of social conditions. This position is unique because romantic love is promoted as a cultural rather than social universal. We argue that culture, social, and psychological phenomena are too frequently conflated and their core definitional features underdefined by researchers. Culture refers to learned practices that have collectively shared meanings to the members of a society. Under social conditions in which romantic love does not confer reproductive and health advantages to a mother and child, it will often be suppressed, undeveloped, and rejected as a cultural component. Through a cross-cultural study, we show that female status and family organization are important features that help in regulating the sociocultural importance of romantic love as a basis for marriage.